Toward Fully‐Fledged Quantum and Classical Communication Over Deployed Fiber with Up‐Conversion Module. Issue 7 (4th June 2021) - Bacco, Davide; Vagniluca, Ilaria; Cozzolino, Daniele; Friis, Søren M. M.; Høgstedt, Lasse; Giudice, Andrea; Calonico, Davide; Cataliotti, Francesco Saverio; Rottwitt, Karsten; Zavatta, Alessandro
Abstract: Quantum key distribution (QKD), the distribution of quantum secured keys useful for data encryption, is expected to have a crucial impact in the next decades. However, despite the notable achievements accomplished in the last 20 years, many practical and serious challenges are limiting the full deployment of this novel quantum technology in the current telecommunication infrastructures. In particular, the co‐propagation of quantum signals and high‐speed data traffic within the same optical fiber is not completely resolved, due to the intrinsic noise caused by the high‐intensity of the classical signals. As a consequence, current co‐propagation schemes limit the amount of classical optical power in order to reduce the overall link noise. However, this ad‐hoc solution restrains the range of possibilities for a large scale QKD deployment. Here, a new method, based on up‐conversion assisted receiver, for co‐propagating classical light and QKD signals is proposed and demonstrated. In addition, its performances are compared with an off‐the‐shelf quantum receiver, equipped with a standard single‐photon detector, over different lengths of an installed fiber link. The authors' proposal exhibits higher tolerance for noise in comparison to the standard receiver, thus enabling the distribution of secret keys in the condition of 4 dB‐higher classical power. Abstract : An up‐conversion‐assisted receiver is proposed to detect weak quantum signals that are co‐propagated with classical optical power, in a dense wavelength division multiplexing (DWDM) scheme exploiting an installed fiber‐optic link. As compared to current telecom detectors, an enhancement of 4 dB in the classical power tolerated by quantum communication is successfully demonstrated, thus improving its compatibility with existing telecom infrastructures.